Multiple source analysis of interictal spikes: goals, requirements, and clinical value - Scherg, Michael; Bast, Thomas; Berg, Patrick (Journal of clinical neurophysiology, 1999)
When evaluating interictal spikes using dipole source analysis it is important to account for multiple sources and the overlapping background EEG. Analyses of spike peaks may be modeling only propagated sources. Careful filtering of averaged spike data and multiple source analysis can provide useful information about the onset of epileptiform activity. A forward high-pass filter can help to enhance the initial spike activity during onset over the propagated activity. These points are illustrated with examples of a temporal, a parietal, and a frontal averaged spike. Multiple source analysis was applied using a genetic algorithm and a sequential strategy, in one case including a model of background alpha activity. Multiple source analysis could model sources describing the onset activity that were distinct in location and orientation from the propagated activity. In all cases, the prominent peak on the scalp was dominated by the contribution of propagated sources. Clinical interpretation benefits from an approach that combines the temporal evolution of EEG scalp topography and multiple source activities with the information from localization and orientation of equivalent dipole sources to identify the cortical generators underlying the earliest phase of interictal spikes.
Gesehen am 15.03.2021